Value chain analysis of algal bioenergy and carbon capture integrated with a biotechnology innovation. (10th April 2018) - Ou-Yang, Chao; Chen, Hsiao-Wei; Ho, Chi-Hung; Chou, Ju-Ching; Yuan, Yu-Ting; Ho, Chen-Lung; Hsueh, Hsin-Ta; Chen, Shui-Tein; Liao, Pei-Chun; Chao, Louis Kuoping
Abstract: In this study, an algal carbon dioxide (CO2 ) capture system was improved by adjusting the flashing frequency of light emitting diodes in a photobioreactor to enhance algal growth and the absorption of CO2 from the flue gas of a coal-fired power plant. This system comprised 2016 transparent 15 L containers with a total volume of 28, 728 L. The results of this study indicate that each hectare of algae production can capture 231.4 tons of CO2 per year, which is a three-fold increase compared to previous studies. Also, even after extraction of C-phycocyanin from Arthrospira platensis, the residue of A. platensis possessed a heat of combustion exceeding 20, 920 kJ/kg, and could be co-combusted with coal to recover more energy. After enzymatic hydrolysis and a biochemical analysis, it was determined that C-phycocyanin has anti-tumour effects against human oral and alveolar cancer. This study aimed to determine the feasibility of the algal carbon capture method as a renewable energy technology and improve its energy efficiency. A value chain analysis and Monte Carlo simulation was used for the evaluation, to consolidate existing approaches of algal CO2 capture and develop them beyond the laboratory scale. Furthermore, we aimed to demonstrate the beneficial application of algal biomass production beyond carbon sequestration so as to lower the costs of carbon sequestration. The results of this study suggest that this approach has high commercialisation potential. Graphical abstract: Image 1 Highlights: The innovative technology improved the overall value chain of bio-based CO2 capture. A potentially viable carbon capturing system was developed. This was the largest pilot-scale experimental biofuel producing module in Taiwan. Methods to maximize potential biofuel production were evaluated.